Studi Ruang Pembelajaran Kolaboratif Studio-Based Classroom untuk Kampus Kreatif - Karna Mustaqim; Jhon Viter Marpaung; Daffa Farras Dienputra; Raysha Kantiliana Maheswari; Adisti Ananda Yusuf (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The transformation of national universities into global-minded institutions should necessitate a design concept that integrates the design of learning facilities and learning outcomes. This research aims to seek design concepts that support research and learning in a hybrid learning environment. The research method is carried out from practice-based research as a way of research through design to build a conception of future-oriented learning classroom design. As a result, this research output is outlined in the conceptualization of integrated classroom design whose learning is collaborative by applying studio-based classroom design on the campus of Esa Unggul University, Citra Raya branch, Tangerang.